Influence of teachers motivational perceptions, motivational strategies, efficacy and beliefs in students’ academic achievement at Oman Public Schools - Al-Rawahi, Talal Salim Sangoor (2017)
Motivation is an essential factor which affects students’ participation and engagement in their classwork and academic achievement and grades. The main purpose of this research is to identify the level of teacher motivational perception, motivational strategy, self-efficacy, general beliefs and students’ academic achievements. Specifically, it is focused on investigating; i) the relationship between teacher motivational strategy, self-efficacy, general beliefs and students’ academic achievements. ii) The differences of motivational perception, motivational strategy, motivational strategy, self-efficacy and general beliefs based on genders, class level teach and teaching experiences. The study was based on the quantitative method in nature with a correlational survey design using questionnaires of Teacher Motivational Perception (TMP) and Teacher Motivational Strategies (MS) by Hardre’ (2008). A pilot study have been conducted on 30 teachers which indicates the scores of Cronbach's Alpha (α=.74) of TMP and (α=.86) of MS. The study sample comprised of 135 Welayate Sumail, Al Dakhelia Governorate teachers, who taught the 11th and 12th class level in 9 of the secondary public schools. Overall, there were 64 male and 71 female teachers that taught essential subjects with five years of minimum teaching experience. The results showed that there was a moderate teachers’ motivational perception (M=3.29, SD=.327), high level of motivational strategies (M=4.38, SD=.974), high level of teachers’ self-efficacy (M=4.10, SD=.548), high level of general beliefs (M=4.22, SD=.545) and moderate level of students’ academic achievements (M=66.29, SD=7.11). In addition, there is a positive and significant relationship between teachers' motivational strategies and students’ academic achievements (11th; r=.285 p<0.05), (12th; r=.333 p<0.05), a positive and significant relationship between relationship between self-efficacy with students’ academic achievements (r=0.295, p= .018), positive and significant relationship between general beliefs with students’ academic achievements in malleable (r=0.427, p= .001). On the other hand, the results showed that there was no significant relationship between teachers' transient beliefs with students’ academic achievements (r=0.154, p=.226). However, there were significant differences of teacher motivational perception based on gender (t=1.137, p=.032) and class levels (F=3.928, p=.019) but no significant differences (F =2.008, p>0.05) in teaching experiences. Meanwhile, there were no differences of teacher motivational strategies based on gender (t=1.35, p=.133), class level (F=.103, p=.902) and teaching experiences (F=.681, p=.954). The study showed different levels of perceptions and beliefs but agreed on the importance of studying motivation from the perspective of reasons, strategies, self-efficacy and beliefs and how it was correlated to student academic achievements. The findings of this study may serve as a platform for school authorities, administrators and policymakers in developing students’ motivation and motivational strategies that can be used in classrooms practices at Oman Public school.